Fear conditioning and extinction in alcohol dependence: Evidence for abnormal amygdala reactivity. (8th November 2019) - Muench, Christine; Charlet, Katrin; Balderston, Nicholas L.; Grillon, Christian; Heilig, Markus; Cortes, Carlos R.; Momenan, Reza; Lohoff, Falk W.
Abstract: Fear conditioning and extinction (FCE) are vital processes in adaptive emotion regulation and disrupted in anxiety disorders. Despite substantial comorbidity between alcohol dependence (ALC) and anxiety disorders and reports of altered negative emotion processing in ALC, neural correlates of FCE in this clinical population remain unknown. Here, we used a 2‐day fear learning paradigm in 43 healthy participants and 43 individuals with ALC at the National Institutes of Health. Main outcomes of this multimodal study included structural and functional brain magnetic resonance imaging, clinical measures, as well as skin conductance responses (SCRs) to confirm differential conditioning. Successful FCE was demonstrated across participants by differential SCRs in the conditioning phase and no difference in SCRs to the conditioned stimuli in the extinction phase. The ALC group showed significantly reduced blood oxygenation level‐dependent responses in the right amygdala during conditioning (Cohen's d = .89, P (FWE) = .037) and in the left amygdala during fear renewal (Cohen's d = .68, P (FWE) = .039). Right amygdala activation during conditioning was significantly correlated with ALC severity ( r = .39, P (Bonferroni) = .009), depressive symptoms ( r = .37, P (Bonferroni) = .015), trait anxiety ( r = .41, P (Bonferroni) = .006), and perceived stress ( r = .45, P (Bonferroni) = .002). Our data suggest that individuals with ALC have dysregulated fear learning, in particular, dysregulated neural activation patterns, in the amygdala. Furthermore, amygdala activation during fear conditioning was associated with ALC‐related clinical measures. The FCE paradigm may be a promising tool to investigate structures involved in negative affect regulation, which might inform the development of novel treatment approaches for ALC. Abstract : Individuals with alcohol dependence showed significantly reduced BOLD responses in the right amygdala during fear conditioning and in the left amygdala during fear renewal. Right amygdala activation during conditioning was significantly correlated with alcohol dependence‐related clinical measures, including alcohol dependence severity, depressive symptoms, trait anxiety, and perceived stress. These findings indicate that the FCE paradigm may be a promising tool to investigate structures involved in negative affect regulation, which might inform the development of novel treatment approaches for alcohol dependence.